Fmrp regulates neuronal balance in embryonic motor circuit formation - Barker, Chase M.; Miles, Kaleb D.; Doll, Caleb A. (Frontiers in Neuroscience, 2022)
Motor behavior requires the balanced production and integration of a variety of neural cell types. Motor neurons are positioned in discrete locations in the spinal cord, targeting specific muscles to drive locomotive contractions. Specialized spinal interneurons modulate and synchronize motor neuron activity to achieve coordinated motor output. Changes in the ratios and connectivity of spinal interneurons could drastically alter motor output by tipping the balance of inhibition and excitation onto target motor neurons. Importantly, individuals with Fragile X syndrome (FXS) and associated autism spectrum disorders often have significant motor challenges, including repetitive behaviors and epilepsy. FXS stems from the transcriptional silencing of the gene Fragile X Messenger Ribonucleoprotein 1 (FMR1), which encodes an RNA binding protein that is implicated in a multitude of crucial neurodevelopmental processes, including cell specification. Our work shows that Fmrp regulates the formation of specific interneurons and motor neurons that comprise early embryonic motor circuits. We find that zebrafish fmr1 mutants generate surplus ventral lateral descending (VeLD) interneurons, an early-born cell derived from the pMN domain. As VeLD interneurons are hypothesized to act as central pattern generators driving the earliest spontaneous movements, this imbalance could influence the formation and long-term function of motor circuits driving locomotion. fmr1 embryos also show reduced expression of proteins associated with inhibitory synapses, including the presynaptic transporter vGAT and the postsynaptic scaffold Gephyrin. Taken together, we show changes in embryonic motor circuit formation in fmr1 mutants that could underlie persistent hyperexcitability.